Globalization and Contestation: The New Great Counter-Movement - Munck, Head of Civic Engagement Dublin City University and Visiting Professor of Development Studies University of Liverpool and St Mary's University Nova Scotia Ronaldo; Munck, Ronaldo (Routledge, 2006)
Globalization is undoubtedly the great overarching paradigm of our era. However, there is still little agreement on what globalization actually ‘is’ and some do not accept that it ‘is’ anything at all. This new book addresses the contestation of globalization by the anti- or counter-globalization movement. To contest means to challenge, to call into question, to doubt, to oppose and to litigate. This study shows how globalization is ‘contestable’ in many different ways and how the counter-movements we have seen emerging over the last decade also ‘bear witness’ on behalf of an alternative human future. Ronaldo Munck presents an overarching framework that allows us to understand how globalization and its contestation are inextricably bound up with one another. This volume insightfully explores a number of case studies, including: the battle of Seattle in 1999 the World Social Forum peasant internationalism environmental movements and reactionary movements including: the US Patriot's movement, Islamic fundamentalist movements and other nationalist movements. Globalization and Contestation will be of great interest to all students and scholars of international relations, politics and of globalization and global governance in particular.
Keywords: countermovement; globalization; political economy; political science

Beyond Globalization: Capitalism, Territoriality and the International Relations of Modernity - Lacher, Hannes (Routledge, 2006)
Hannes Lacher presents a new critical social theory of international relations that integrates sociology, history and political geography to understand the formation and development of modern international relations. Far from implying a return to state-centrist Realism, this essential new volume leads us towards a critical social theory of international relations that questions the prevailing conceptions of the modern international political economy as a collection of nationally bounded spaces more fundamentally than ever before. It also shows us that capitalist modernity itself was, from the beginning, characterized by the dualism of global economic integration and the fragmentation of political space, which actually stems from the divergent origins of capitalism and territorial sovereignty. This book will be of great interest to al students of historical sociology, political geography, international relations and political science.
Keywords: international political economy; international relations

Vulnerability and violence: the impact of globalisation - Kirby, Peadar (Pluto, 2006)
'Vulnerability' is now a key term in globalisation studies. It is used to describe how globalisation impacts on individual security, local communities and even global flows of trade, finance and investment. Yet there has been little attempt to interrogate the term and what it is trying to express about globalisation.Peadar Kirby examines what is really meant by 'vulnerability' and links it to new forms of violence that have resulted from decreased security and social cohesion. He argues that vulnerability and violence are characteristic features of a new world order dominated by neoliberal globalisation. Illustrating his argument with a wealth of examples taken from all over the world -- from the sudden collapse of the middle class in Argentina to increased levels of poverty internationally -- he offers a robust theoretical grounding that will be of use to anyone studying vulnerability and violence and their relation to contemporary globalisation.
Keywords: globalization; globalization - economic aspects; globalization - social aspects; international security; national security; political freedom & security; violence; violence in society

Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation - Polanyi Levitt, Kari; McRobbie, Kenneth (Black Rose Books, 2006)
Karl Polanyi’s belief that the greatest threat to freedom was a poorly administered economy led him to an economics that was more existential and human-centered. Part I of this book develops Polanyi’s thinking for its significance today through a selection of papers on re-reading his major work entitled The Great Transformation. Part II looks at the life and work of Ilona Duczynska (Polanyi’s wife), political activist, writer and translator and important influence over Karl and his work. Kenneth McRobbie, a poet and historian who teaches at the University of British Columbia, is the editor of Humanity, Society and Commitment. Kari Polanyi Levitt, emeritus professor at McGill University, is the editor of The Life and Work of Karl Polanyi.
Keywords: autobiography; biography; business & economics

Lavoro e società industriale. Da Adam Smith a Karl Polanyi - Rosa, Michele La; Rizza, Roberto; Zurla, Paolo (FrancoAngeli, 2006)
KM translate: The volume aims to provide a contribution to the knowledge of the ways of birth and consolidation of the sociological discourse on the economy, at work and their transformations connected to the process of industrialization. The goal, mainly educational, is pursued through the analysis of the contributions that Karl Marx, Emile Durkheim, Max Weber, Joseph Schumpeter, Karl Polanyi, Frederick Taylor and Elton Mayo have offered in this regard. The treatment of these authors, whose total or partial belonging to the sociological context is out of the question, was preceded by a brief analysis of others such as Adam Smith, Charles Babbage and Andrew Ure who, although not strictly belonging to this disciplinary area,
Keywords: DURKHEIM, Emile; MARX, Karl, 1818-1883; SMITH, Adam, 1723-1790; business & economics - labor; economic sociology; industrial revolution; industrialization; sociology of work